2019
DOI: 10.1108/jpbafm-06-2018-0054
|View full text |Cite
|
Sign up to set email alerts
|

Are not-for-profit employees more willing (or likely) to be whistleblowers?

Abstract: Purpose The purpose of this paper is to investigate whether intention to report fraud varies by organization type or fraud type. Employees who self-select into not-for-profits may be inherently different from employees at other organizations. Design/methodology/approach The authors conduct a 2 × 2 experiment in which (n=107) individuals with a bookkeeping or accounting background respond to a fraud scenario. Analysis of covariance models are used for data analysis. Findings The authors find evidence that n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 80 publications
1
10
0
Order By: Relevance
“…All 14 of these studies found a positive relationship between the severity of the wrongdoing and whistleblowing intentions. The type of wrongdoing was positively associated with whistleblowing intentions in four studies (Lee et al, 2004;Somers and Casal, 2011;Brink et al, 2017;Taylor, 2019), although Scheetz and Wilson (2019) found that all types of wrongdoing were positively associated with whistleblowing among not-for-profit employees. Six studies (Brooks and Perot, 1991;Lee et al, 2004;Rothwell and Baldwin, 2006;Grube et al, 2010;Lyndon et al, 2012) examined the extent to which the frequency of wrongdoing was linked to whistleblowing intentions.…”
Section: Characteristicsmentioning
confidence: 89%
“…All 14 of these studies found a positive relationship between the severity of the wrongdoing and whistleblowing intentions. The type of wrongdoing was positively associated with whistleblowing intentions in four studies (Lee et al, 2004;Somers and Casal, 2011;Brink et al, 2017;Taylor, 2019), although Scheetz and Wilson (2019) found that all types of wrongdoing were positively associated with whistleblowing among not-for-profit employees. Six studies (Brooks and Perot, 1991;Lee et al, 2004;Rothwell and Baldwin, 2006;Grube et al, 2010;Lyndon et al, 2012) examined the extent to which the frequency of wrongdoing was linked to whistleblowing intentions.…”
Section: Characteristicsmentioning
confidence: 89%
“…Rationalization is an important com ponent of many cheating. Rezaee & Wang (2019) and Scheetz & Wilson (2019) state that rationalization is an important compo nent in many frauds. Accounting Fraud oc curs because of a contributing factor, namely rationalization (Trompeter et al, 2014).…”
Section: Figure 2 the Regression Results For Regression Equations I Ii Iii And Ivmentioning
confidence: 99%
“…Accounting fraud occurs due to bad habits. Bad habits that are intended to be associated with gambling, drugs, alcohol, and expensive items are negative in nature (Rezaee & Wang, 2019;Scheetz & Wilson, 2019). These bad habits encourage someone to commit an unethical action or behaviour.…”
Section: Questionnaires Distributed 450mentioning
confidence: 99%
See 1 more Smart Citation
“…We contend that disclosure transparency, will provide positive signals about CEO and NFP organization integrity and trustworthiness that will reap long-term reputational benefits. Recent research also suggests that ethical behavior is also especially important to NFP employees (Scheetz and Wilson, 2019), so transparent reporting should enhance the internal ethical environment as well.…”
Section: Contributions To Practicementioning
confidence: 99%